Agricultural activity during the formative period in the central Andes - Silva, Jorge (1980)
Archeology has been proving for decades that the historical development that took place in the Andes, before the European invasion, is quite old and with very particular peculiarities. The discussion about a probable Mesoamerican or transpacific influence on the Andean socio-economic structure has been left behind and outdated. This applies, equally, to those positions that try to claim for themselves certain geographical regions as the basic nucleus from which the Andean civilization arose.